ANALISIS PEMASARAN KARET (Havea brasiliensis) DI KELURAHAN PANGKALAN BUNUT KECAMATAN BUNUT KABUPATEN PELALAWAN - Sitri Ningsih; Eliza '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to (1) determine the rubber marketing channels and institutions involved in the marketing process, (2) analyze the cost, margin, profit on each bokar marketing agency, part received by farmers and marketing efficiency bokar, (3) determine the relationship between farmers' patron-client with rubber traders in Sub Base Bunut. This study uses survey and sampling method is purposive sampling farmers with the following requirements: age 20-25 years old rubber trees, varieties of local varieties and land area of 1 ha. Sampling methods Snaw Ball merchants. Total sample farmers and traders of 30 people by 4 people. The results obtained by the channel 1 from farmers to traders or 43.33% then traders to large merchant wholesalers continued to plant. Channel 2 from farmers to wholesalers and then to the factory. Total margin marketing channel 1 is Rp 3.500.00 / kg, marketing profit of Rp. 10.812,34 / kg, the share of the farmer is 74.075% and 19.91% efficiency which is marketing. Marketing channel 2 margin of Rp. 3.000.00 / kg, marketing profit of Rp. 11.823,72 / kg, the share of the farmers are 77.78% and 12.42% efficiency which is marketing. The relationship between farmers and traders the dominant concerns of family connections, so that farmers have a high dependence on traders. Keywords: Marketing Channels, Patron-Client, Rubber Farmers, Traders.